In Sputnik's Shadow : The President's Science Advisory Committee and Cold War America - Wang, Zuoyue, 1963- (Book collections on Project MUSE., 2008)
In today's world of rapid advancements in science and technology, we need to scrutinize more than ever the historical forces that shape our perceptions of what these new possibilities can and cannot do for social progress. In Sputnik's Shadow provides a lens to do just that, by tracing the rise and fall of the President's Science Advisory Committee from its ascendance under Eisenhower in the wake of the Soviet launching of Sputnik to its demise during the Nixon years. Members of this committee shared a strong sense of technological skepticism; they were just as inclined to advise the president about what technology couldn't do-for national security, space exploration, arms control, and environmental protection-as about what it could do. Zuoyue Wang examines key turning points during the twentieth century, including the beginning of the Cold War, the debates over nuclear weapons, the Sputnik crisis in 1957, the struggle over the Vietnam War, and the eventual end of the Cold War, showing how the involvement of scientists in executive policymaking evolved over time. Bringing new insights to the intellectual, social, and cultural histories of the era, this book not only depicts the drama of Cold War American science, it gives perspective to how we think about technological advancements today.